Pelatihan Perhitungan Tarif Biaya Overhead Pada Produksi Craft Fashion Pada Komunitas Dekrasnada Tangerang Selatan Untuk Menghindari Overbudgeting di Produksi Bahan Dagangan - Paramitha, Diky Paramitha; Novita Nugraheni; Etik Ipda Riyani; Dwirini; Eka Wirajuang Daurrohmah; Zulkifli Sultan (Celebes Journal of Community Services, 2024)
Indonesia's economy is currently experiencing very good progress which is influenced by many factors, one of which is the contribution of the development of Micro, Small, and Medium Enterprises (MSMEs). MSMEs have a considerable contribution, especially in creating jobs nationally. Although the number and contribution are quite large, there are still many MSMEs that have problems in terms of Human, Accounting, Managerial and Financial data sources. Currently, many are experiencing difficulties in terms of accounting, especially in terms of calculating overhead cost rates which will later affect the cost of production. The problem of calculating overhead costs which will later be related to the cost of production is one of the problems faced by the Regional National Handicraft Council Community (Dekrasnada) in Pamulang District, South Tangerang City, Banten Province. The importance of the overhead cost tariff calculation process encourages the implementation of community service activities in the form of Training on Overhead Cost Tariff Calculation in Craft Fashion Production in the South Tangerang Dekrasnada Community to Avoid Overbudgeting in the Production of Merchandise to provide insight and knowledge related to the calculation of overhead tariffs in production so that overbudgeting in production can be minimized.